THE REPRCUSSION OF SPORT PROGRAMS OF THE YOUTH CENTER ON THE DEVELOPEMENT OF GOOD CITIZENSHIP VALUES - KHADER, Ali; ben omer, mourad (sports creativity, 2025)
The research generally talks about one of the sport roles as having a big influence on the society .the aim of our research is investigate and to know this impact through its principles and values to develop good citizenship .in addition the contribution of sport in opening new doors of knowledge in this field also offering new future vistas .i followed the descriptive method because i think it is the most convenient and suitable i have selected 3000 participants from tow different stats from the youth center of djelfa msila as a method gather information for tis research .i used the survey in which we divided it into 4categories each ten questions orderly serve a hypo thesis .the result were successful and valid therefore the youth center programs have great effect in the development of good citizenship